Rekonstruksi Pembuktian Unsur Percobaan dalam Konteks Perbarengan Tindak Pidana - Jason Thimoty (Sanskara Hukum dan HAM, 2026)
The issue of proving the elements of criminal attempt within the context of concurrence of offenses (concursus delictorum) continues to generate inconsistency in Indonesian criminal court practice. This study aims to analyze the fulfillment of the elements of criminal attempt in a case involving potential concurrence of offenses and to evaluate the appropriateness of the indictment construction applied. This research employs a normative juridical method using statutory, conceptual, and case approaches. Conceptually, the population consists of court decisions involving elements of criminal attempt and concurrence of offenses, with purposive sampling applied to select a relevant case for in-depth analysis. Data were collected through literature review and document analysis and examined using qualitative juridical analysis by aligning legal norms with judicial facts. The findings indicate that the normative elements of criminal attempt were fulfilled; however, they were not explicitly incorporated into the indictment within the framework of concurrence of offenses. The novelty of this research lies in its integrative analysis between the doctrine of criminal attempt and the theory of concursus delictorum in assessing indictment construction. The study implies the necessity of more comprehensive indictment drafting to ensure consistency in the application of substantive criminal law and transparency in criminal liability.